BINDING MATERIALS FOR CREATING COAL GRANULES AND THEIR COLLOID-CHEMICAL CHARACTERISTICS - Mehmonxonov, Mansurxon; Paygamov, Rahimjon; Bahronov, Hayot; Abdikamalova, Aziza; Eshmetov, Izzat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. This article examines binders necessary for formation of coal-resin granules and their colloidal-chemical characteristics. Data analysis shows that viscosity and coke residue are key parameters for binders. Optimum viscosity values ensure the required plasticity of the mixture for granulation, and a coke residue content of 9-15% contributes to the formation of carbon bridges without reducing adsorption activity. High viscosity adhesives such as asphaltene and bitumen require the use of solvents to reduce viscosity. The use of auxiliary substances, such as heavy gas oil and diesel fuel, makes it possible to obtain formulations with low viscosity and optimal coke residue content.